Towards multilingualism in global health - Ralph Hurley O’Dwyer; Rebecca C. Stout; Émilie S. Koum Besson; Amaya L. Bustinduy; Máire A. Connolly (Globalization and Health)
Abstract A forgotten aspect of the decolonizing global health movement is the impact of monolingualism on the practice of medicine and global health. Thousands of languages are spoken worldwide yet remarkably few are used in these fields. English, in particular, plays an extraordinarily dominant role. The status of English as the global medical lingua franca perpetuates inequities in research, medical education and healthcare delivery, disproportionately affecting many low-and middle-income countries (LMICs). This linguistic hegemony creates barriers to accessing health information for minoritized populations and discriminates against researchers from non-native English-speaking backgrounds. Even the speakers of major world languages such as Arabic and Hindi are marginalized, with little research published in these languages and medical education generally unavailable in them. This inequality affects patients’ ability to receive care and access information in their own languages and contributes to mistrust and exclusion. This is particularly the case in formerly colonized countries where exploitative medical practices remain a painful legacy. A paradigm shift is urgently needed in the global health field to address these inequities. We propose solutions include expanding foreign language education, supporting minoritized languages in health promotion, and mandating the dissemination of research output in the languages of the studied populations. Ultimately, the languages we choose to use as global health practitioners shape power dynamics, determine whose voices are heard, and impact the effectiveness of our actions. Without urgent and systemic change, the dominance of a few languages, particularly English, risks perpetuating inequities and excluding those most in need of inclusion.